A study on the impact of childhood obesity on health-related physical fitness through motor coordination–related functional pathways - Zhao, Deqiang; Chen, Xiaoxiao; Pan, Xiang; Wang, Shuwan; Wang, Jiameng; Hu, Haixia; Zhang, Yanfeng (Frontiers in Nutrition, 2026)
ObjectiveThis study aimed to investigate the impact of childhood obesity on health-related physical fitness performance and to examine the mediating role of motor coordination ability as a behavioral functional pathway in this relationship.MethodsA cross-sectional study design was employed. In June 2025, 431 children aged 7–14 years (204 in the obesity group, 227 in the normal-weight group) were recruited from Weifang City, Shandong Province, China. Body composition (BMI and PBF) was measured using a bioelectrical impedance analyzer. Health-related physical fitness index was assessed according to the Chinese National Student Physical Fitness Standard and synthesized into a standardized physical fitness index. Motorcoordination was evaluated using the Movement Assessment Battery for Children-2 (MABC-2), which reflects behavioral motor performance. Statistical analyses included independent samples t-tests, Pearson correlation analysis, hierarchical regression analysis, and the Bootstrap method for mediation effect testing.ResultsBoth the physical fitness index and the motor coordination index were significantly lower in obese children compared to normal-weight children (Cohen’s d = 0.31–0.34). BMI and PBF showed significant negative correlations with the physical fitness index. After controlling for area (urban/rural), gender, and age, both BMI and PBF independently and negatively predicted the physical fitness index. Mediation analysis indicated that motor coordination played a statistically significant partial mediating role in the relationship between BMI and the physical fitness index (indirect effect = −0.060, 95% CI [−0.105, −0.048]), as well as between PBF and the physical fitness index (indirect effect = −0.036, 95% CI [−0.052, −0.022]).ConclusionChildhood obesity is closely associated with decreased health-related physical fitness, with PBF being a more stable predictor than BMI. Motor coordination represents one behavioral pathway that may partially explain the association between body composition and physical fitness performance. Given the cross-sectional design, these findings reflect statistical associations rather than causal or neuromotor mechanisms. Longitudinal and intervention studies are needed to further verify directionality.